The Role of Practicing Yoga and its Physiological Benefits - Dubey, Jay Prakash; Tiwari, Archana (International Research Journal of Ayurveda & Yoga, 2023)
Yoga is an ancient Indian science which is claimed that it develop perfect physical, mental and spiritual health. Several scientific studies have been conducted on Yogic practices for several years where it establishes a harmony between mind and body. Yoga practice shows some physiological effects on every system of our body. This article, an attempt has been made to evaluate the possible mechanisms for such physiological, biochemical and psychological effects with references. Yoga is thus described as comprising a rich treasure of physical and mental techniques that can be effectively used to create physical and mental wellbeing. Since its introduction into modern culture, yoga has enjoyed a tremendous growth in popularity as an healthy living.